2019
DOI: 10.2298/vsp170301080s
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities between the symptoms and clinical signs in patients with pulmonary tuberculosis and pneumonia

Abstract: Background/Aim. Tuberculosis in the second decade of the 21st century is an infectious disease with the highest mortality rate. In addition, in developed countries, pneumonia is the major couse of morbidity and mortality in adults. The aim of our study was to point out the differences and similarities between symptoms, laboratory parameters and clinical indicators in patients with pulmonary tuberculosis (PTB) and patients with pneumonia in the general population and in people belonging to the high risk groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
2
3
0
2
Order By: Relevance
“…In this study, among 120 male and 115 female participants, the males were affected significantly more than the females (p<0.01). This sex disparity among the reported PTB case findings corresponds to the findings by Goroh MMD et al [ 5 ], Behr MA et al [ 14 ], Hernández-Garduño E et al [ 15 ], Tostmann A et al [ 17 ], Linguissi LS et al [ 25 ], Zhang X et al [ 26 ] and Smiljić S et al [ 27 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, among 120 male and 115 female participants, the males were affected significantly more than the females (p<0.01). This sex disparity among the reported PTB case findings corresponds to the findings by Goroh MMD et al [ 5 ], Behr MA et al [ 14 ], Hernández-Garduño E et al [ 15 ], Tostmann A et al [ 17 ], Linguissi LS et al [ 25 ], Zhang X et al [ 26 ] and Smiljić S et al [ 27 ].…”
Section: Discussionsupporting
confidence: 86%
“…Although all the age groups were affected, PTB was comparatively more common (p<0.05) in the 25–44 year-old group. Goroh MMD et al [ 5 ], Zhang X et al [ 26 ] and Smiljić S et al [ 27 ] found the same trend in their studies, in which the same age group had the highest number of TB patients, and Linguissi LS et al [ 25 ] reported that the median (IQR) age for PTB patients was 32 (25–46) years. By contrast, Tostmann A et al [ 17 ] reported the highest affected age group to be 15–34 years old, which is partly within the 25–44 year age group but comparatively lower.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Pneumonia and pulmonary TB have some of the same symptoms. However, there are some more specific symptoms that make handling differently for each disease [23]. The main symptom for lung cancer is cough, but it also can be detected by patient behavior [24].…”
Section: Research Methods 21 Lung Disease Symptomsmentioning
confidence: 99%
“…Ovi simptomi na taj način zaslužuju da se preporuče kao indikatori SNTBC dijagnoze u antituberkuloznom dispanzeru. Morbiditet i mortalitet povezan sa kasnom dijagnozom SNTBC može biti smanjena sa ovom strategijom [18,19,20].…”
Section: Rezultatiunclassified